Larval development in the lutjanid subfamily Lutjaninae (Pisces): the Indo-Pacific genus Pinjalo - Leis, Jeffrey M (Zootaxa, 2008)
The larvae of the two species of Pinjalo are described for the first time based on seven specimens of P. pinjalo (4.3–7.5 mm) and 23 specimens of P. lewisi (5.6–15.0 mm) captured in plankton tows and midwater trawls in the eastern Indian and western Pacific Oceans. Identification was confirmed by fin meristics. These deep-bodied, compressed larvae share all the characteristics of lutjanid larvae, and have some of the most well-developed head spination and fin spines of any lutjanids. The robust spines of the dorsal, anal and pelvic fins bear strong serrations. The preopercular spines are particularly enlarged, some bear fine serrations, and the anterior end of the maxilla also has fine serrations: these fine serrations are rare in lutjanine lutjanids. The two species of Pinjalo can be distinguished by the meristics of dorsal and anal fins, the relative lengths of the first spine of the dorsal fin and the spine of the pelvic fin. The larvae have distinctive pigment on the dorsal fin, head and caudal peduncle. The body shape, pigment pattern, fin-spine morphology, and the fine serrations on the head spines of the two Pinjalo species are very similar to the larvae of Lutjanus erythropterus and L. malabaricus, and may indicate a close relationship among these four species.